Application The Aikipressure Techniques to Improve The Development of Children with Special Needs: A Qualitative Study - Wahyuningsih, Istiqomah Risa; Kustiyati, Sri; Imania, Dika Rizki; Asadullah, Abdullah (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2021)
Purpose: describe how to apply aikipressure techniques to improve the development of children with special needs in the development clinic health center, Sukoharjo, Central Java, Indonesia. Methodology: a descriptive qualitative design. Determination of research subjects by purposive sampling includes the following criteria: 1) mothers who have children with special needs are members of the development clinic health center; 2) mothers who want to give acupressure therapy to their children; 3) mothers who are willing to be respondents; 4) mothers who are willing to provide data according to the research questions. The research was conducted in September-November 2021. The research site was in the development clinic health center, Sukoharjo, Central Java, Indonesia. The time of data collection was carried out for 1 month with monitoring carried out every 1 week. The aikipressure technique was carried out every day by the parents and accompanied by the research team. Results: Interviews were conducted with 10 main informants, 1 key informant and 1 supporting informant. Characteristics of the main informants, namely 1 male informant and 9 female informants, aged between 27- 44 years, the majority are housewives, the age of children is in the range of 2.5-14 years. Characteristics of informants based on the condition of the child, namely 1 child hydrocephalus, 5 children with cerebral palsy, 2 children with hyperactivity and 2 children with Down syndrome. The advantages of aikipressure are simple, effective and efficient. Applications/Originality/Value: The novelty of this research is the application of aikipressure therapy in improving the development of children with special needs. Aikipressure therapy can be done by parents independently.